PEMIKIRAN SOSIAL-POLITIK KIAI HAJI SAIFUDDIN ZUHRI - Hasna Whidia; Nabila Niranti; Silfi Windriyani (CV. Adiba Aisha Amira, 2024)
This research aims to know and analyze in depth the thoughts of Prof. K.H. Saifuddin Zuhri, an influential religious and political figure in Indonesia. He was born in 1919, in Purwokerto, Banyumas, Central Java. The focus of this research is more on Prof. K.H. Saifuddin Zuhri's thoughts on social and political aspects. The research method used in this research is literature study. The data obtained comes from the collection and analysis of various literature sources related to the thoughts of Prof. K.H. Saifuddin Zuhri. These sources are in the form of books, journals, articles that have to do with the thoughts of Prof. K.H. Saifuddin Zuhri. The data obtained is then researched, analyzed, and described into narratives and compiled into a complete picture of Prof. K. H. Saifuddin Zuhri's thoughts in the social and political realms. The results showed that Prof. K. H. Saifuddin Zuhri's thought has a significant contribution to the development of Islamic thought in Indonesia, he emphasizes the importance of education as a means to build an advanced and civilized society. In addition, he also emphasizes the importance of tolerance between religious communities and moderate Islam which will foster moderation in religion. In the political context, he supported the guided democratic system and played an active role in fighting for Indonesian independence. In addition, his Islamic nationalism thought shows the harmonization between Islamic values and the spirit of nationality. This research concludes that the thoughts of Prof. K. H. Saifuddin Zuhri are relevant to be studied, especially in the context of Indonesia today. His thoughts can be an inspiration for the younger generation to build a just, prosperous and dignified society and respect each other